Vehicle–Bridge Interaction Dynamic Analysis of Continuous Rigid Frame Composite Box Girder Bridge with Corrugated Steel Webs under Seismic Excitation - Peng Qiao; Chen Ma; Chang-Jiang Duan; Hao Lei; Heng Zhao; Jun He (Advances in Civil Engineering)
To study the vehicle–bridge interaction (VBI) of highway bridges under seismic excitation, a vehicle–bridge couple analysis method based on Ansys is proposed. The 1/2 vehicle model and space beam element model were established to analyze the VBI response of Lanzhou Xiaoshagou bridge. The self-excited excitation of the system is represented by road surface irregularity randomness, while the external excitation is represented by an earthquake. The impact of seismic types, seismic direction, seismic intensity, vehicle speed, and road surface irregularity on the bridge vibration under the vehicle–bridge coupling during an earthquake is thoroughly analyzed. The results reveal that the type of earthquake significantly influences the dynamic response of the bridge, showing a minimum difference of 31.4%. The intensity of the earthquake is positively correlated with the dynamic response of the bridge. Longitudinal and vertical earthquakes have a more noticeable effect on the bridge’s vertical vibration compared to lateral earthquakes. The ratio of the bridge response under vertical or longitudinal seismic excitation to the response of lateral earthquakes ranges from 1.50 to 26.61. Vehicle speed, road irregularity grade, and randomness have a negligible impact on the dynamic response of vehicle–bridge interaction under an earthquake, accounting for less than 3%. These findings indicate that the analysis of earthquake-bridge vibration can simplify the VBI analysis for continuous rigid frame composite box girder bridges with corrugated steel webs under seismic conditions.